Charge dynamics in hybrid and organic-inorganic light harvesting thin films followed with femtosecond transient absorption spectroscopy - Minda, Iulia (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017